1999
DOI: 10.1200/jco.1999.17.3.855
|View full text |Cite
|
Sign up to set email alerts
|

Management of Breast Cancer During Pregnancy Using a Standardized Protocol

Abstract: Breast cancer can be treated with chemotherapy during the second and third trimesters of pregnancy with minimal complications of labor and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(99 citation statements)
references
References 15 publications
0
95
0
4
Order By: Relevance
“…2 Breast cancer surgery during pregnancy had been shown to be safe in 18 patients with pregnancy-associated breast cancer (PABC). 9 Radiotherapy is contraindicated during pregnancy, so mastectomy may be more preferred than breast conservation surgery. 2,5 Although Kal and Struikmans 6 reported that pregnancy was not contraindicated to RT in patients with breast cancer, they also reported that irradiation of maternal breast or chest wall exposes the fetus to 0.05 to 0.15 Gy, which is within the threshold dose that can cause fetal malformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Breast cancer surgery during pregnancy had been shown to be safe in 18 patients with pregnancy-associated breast cancer (PABC). 9 Radiotherapy is contraindicated during pregnancy, so mastectomy may be more preferred than breast conservation surgery. 2,5 Although Kal and Struikmans 6 reported that pregnancy was not contraindicated to RT in patients with breast cancer, they also reported that irradiation of maternal breast or chest wall exposes the fetus to 0.05 to 0.15 Gy, which is within the threshold dose that can cause fetal malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the other patient had the diagnosis at 21 weeks of gestation, pregnancy was ended prematurely because of eclampsia, then CT and RT followed mastectomy. Berry et al 9 reported 24 patients with PABC treated with FAC during the second and third trimesters of pregnancy without any fetal malformation. Ring et al 10 also reported 15 breast cancer patients treated with anthracycline-based regimens during gestation, with 1 IUGR and 2 unspecified respiratory problems.…”
Section: Discussionmentioning
confidence: 99%
“…Though cancer may be diagnosed at a more advanced stage, pregnant patients with a diagnosis of cancer do not appear to have a more aggressive clinical course. A review of breast cancers and lymphomas diagnosed during pregnancy suggests that, matched for age and stage, pregnant women have the same prognosis as nonpregnant controls [26, 27, 28, 29]. Too few cases of lung cancer during pregnancy are reported to allow for a similar comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Given that etoposide was given as part of a chemotherapy regimen, it is difficult to attribute these abnormalities solely to etoposide. Cyclophosphamide and doxorubicin have been administered safely during pregnancy to a large number of women without reported teratogenicity if given after the first trimester, and thus the combination of cyclophosphamide, Adriamycin and vincristine may also be a safe chemotherapeutic regimen for SCLC during pregnancy [27, 44, 45, 67]. No information is available on the use of topotecan during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that with the increase in delayed childbearing age, breast carcinoma diagnosed during pregnancy may become more frequent [94,95]. The role of SLNB in pregnant women with breast cancer is not clear.…”
Section: Relative Contraindicationsmentioning
confidence: 99%